2020
DOI: 10.3390/molecules25235545
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lipid-Based Encapsulation on the Bioaccessibility and Bioavailability of Phenolic Compounds

Abstract: Phenolic compounds (quercetin, rutin, cyanidin, tangeretin, hesperetin, curcumin, resveratrol, etc.) are known to have health-promoting effects and they are accepted as one of the main proposed nutraceutical group. However, their application is limited owing to the problems related with their stability and water solubility as well as their low bioaccessibility and bioavailability. These limitations can be overcome by encapsulating phenolic compounds by physical, physicochemical and chemical encapsulation techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 119 publications
(183 reference statements)
0
37
0
2
Order By: Relevance
“…A previous study of isorhamnetin, an O-methylated quercetin glycoside abundant in onions, suggested that the glucose component in the quercetin glucoside affects its bioavailability [ 22 ]. The application of quercetin is also limited due to stability and solubility issues [ 23 ]. In this study, quercetin solubility and bioavailability were optimized by dissolving in alcohol to a molecular form before dispersing on the dry ingredients.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study of isorhamnetin, an O-methylated quercetin glycoside abundant in onions, suggested that the glucose component in the quercetin glucoside affects its bioavailability [ 22 ]. The application of quercetin is also limited due to stability and solubility issues [ 23 ]. In this study, quercetin solubility and bioavailability were optimized by dissolving in alcohol to a molecular form before dispersing on the dry ingredients.…”
Section: Resultsmentioning
confidence: 99%
“…In this situation, the negative charge of the Cur-RL-Lips surface has been fully shielded by the CS with positive charge. As the Cur-RL-Lips surface becomes fully covered with CS, the surface charge of the liposomes becomes positive and the repulsion among the CS-coated liposomes dominates [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…Liposomes (Lips) are spherically shaped vesicles consisting of a phospholipid bilayer that surrounds an aqueous core; they have attracted widespread attention for their good nutraceutical-loaded property [ 1 ]. Due to their phospholipid bilayer, liposomes are often used for encapsulating both hydrophilic and lipophilic functional ingredients and controlling their release [ 2 , 3 ]. Therefore, they have considerable potential for application in various fields such as functional foods, nutraceutical supplements, and pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…Encapsulation improves the solubilization of hydrophobic functional compounds, protecting them against oxidation and gastrointestinal tract chemical modifications, increasing their bioavailability [ 122 ]. Polyphenols are good candidates to be transported in NEs due to their good lipophilicity and their inherent stability limitations and water insolubility as well as their low bioaccessibility and bioavailability, which can be resolved by lipid encapsulation [ 123 ].…”
Section: Brief Overview Of Nano-encapsulated Polyphenols: Nature and Physiochemical Polymer Benefitsmentioning
confidence: 99%